ZEOLITIZATION OF COAL WASTE AS Cu(II) ION ADSORBENT - Nur Hamid; Daniel Tarigan; Chairul Saleh (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2022)
TZeolization of coal waste was carried out as an adsorbent for Cu(II) ions. Fly ash tailings were collected from Lati Steam Power Plant (SPP) Berau and tested using SEM instruments, X-ray diffraction and AAS. Synthetic zeolites are prepared by hydrothermal reaction under alkaline and alkaline conditions. Characterization of the synthetic zeolite using SEM has formed a zeolite material with a pore size >10 µm and shows an increase in the amount of Na from 3.06% to 11.82%. XRD results show that Na-P1 zeolite is formed at the main top of 2θ16, 30, 33, 10 and 40, 80, and the relative intensities are 34, 31 and 36, respectively. In addition, elemental materials such as silica and mullite are continuously formed on the main top of 2θ26.50 and 26.10, the relative strength of silica is 100, and the relative strength of mullite is 57.9. The optimum adsorption capacity of zeolite for maximum copper ion was 80.330% at pH=4, 97.958% at 150 mg adsorbent weight, and 94.550% at 50 min contact time. The formation of these new materials significantly improved the adsorption capacity of fly ash under optimal conditions of pH = 4, sorbent weight of 150 mg, and contact time of 50 min.